Florid Cystic Endosalpingiosis (Müllerianosis) in Pregnancy - José Morales-Roselló; Loida Pamplona-Bueno; Beatriz Montero-Balaguer; Domingo Desantes-Real; Alfredo Perales-Marín (Case Reports in Obstetrics and Gynecology)
Cystic endosalpingiosis refers to the existence of heterotopic cystic müllerian tissue resembling structures of the fallopian tubes. We report a case of florid cystic endosalpingiosis discovered in a pregnant woman during a scheduled cesarean section and review the current knowledge of this disease. A 30-year-old woman with a twin pregnancy attended the hospital day unit at term. The first twin was in a breech presentation and a cesarean section was scheduled. During the procedure the uterine fundus and part of the body were seen completely seeded with multitude of cyst-like structures resembling hydatids of Morgagni. The immunohistochemistry analysis showed a positive expression for PAX8 (Box-8), CK7, and estrogen and progesterone receptors. The lesions did not disappear after pregnancy. Cystic endosalpingiosis should be always borne in mind, even in pregnancy, when it comes to making the differential diagnosis of a pelvic or systemic multicystic mass.